Intestinal barrier dysfunction mediates Whipple's disease immune reconstitution inflammatory syndrome (IRIS) - Friebel, Julian; Schinnerling, Katina; Geelhaar‐Karsch, Anika; Allers, Kristina; Schneider, Thomas; Moos, Verena (Immunity, Inflammation and Disease, 2022)
Background & Aims Classical Whipple's disease (CWD) affects the gastrointestinal tract and causes chronic diarrhea, malabsorption, and barrier dysfunction with microbial translocation (MT). Immune reconstitution inflammatory syndrome (IRIS) is a serious complication during antimicrobial treatment of CWD. The pathomechanisms of IRIS have not been identified and mucosal barrier integrity has not been studied in patients with IRIS CWD. Methods In 96 CWD patients (n = 23 IRIS, n = 73 non‐IRIS) and 30 control subjects, we analysed duodenal morphology by histology, measured serum markers of MT, and proinflammatory cytokines in biopsy supernatants, and correlated microbial translocation with T cell reconstitution and activation. Results Before treatment, duodenal specimens from patients who later developed IRIS exhibited a more pronounced morphological transformation that suggested a disturbed barrier integrity when compared with the non‐IRIS group. Villous atrophy was mediated by increased apoptosis of epithelial cells, which was insufficiently counterbalanced by regenerative proliferation of crypt cells. Pretreatment deficiencies in the mucosal secretion of proinflammatory cytokines and chemokines (e.g., IL‐6, CCL2) in these patients markedly resolved after therapy induction. High serum levels of lipopolysaccharides (LPS), soluble CD14 (sCD14), and LPS‐binding protein (LBP) combined with low endotoxin core antibody (EndoCAb) titres suggested systemic MT in CWD patients developing IRIS. CD4+ T cell count and activation in IRIS CWD patients correlated positively with sCD14 levels and negatively with EndoCAb titres. Furthermore, the degree of intestinal barrier dysfunction and MT was predictive for the onset of IRIS. Conclusion Prolonged MT across a dysfunctional intestinal mucosal barrier due to severe tissue damage favors dysbalanced immune reconstitution and systemic immune activation in IRIS CWD. Therefore, the monitoring of inflammatory and MT markers in CWD patients might be helpful in identifying patients who are at risk of developing IRIS. Therapeutic strategies to reconstitute the mucosal barrier and control inflammation could assist in the prevention of IRIS. Graphical Prolonged microbial translocation across a dysfunctional intestinal mucosal barrier due to severe tissue damage favors dysbalanced immune reconstitution and systemic immune activation in Whipple's disease immune reconstitution inflammatory syndrome.